2012
DOI: 10.1186/1471-2407-12-391
|View full text |Cite
|
Sign up to set email alerts
|

TMEM45A is essential for hypoxia-induced chemoresistance in breast and liver cancer cells

Abstract: BackgroundHypoxia is a common characteristic of solid tumors associated with reduced response to radio- and chemotherapy, therefore increasing the probability of tumor recurrence. The aim of this study was to identify new mechanisms responsible for hypoxia-induced resistance in breast cancer cells.MethodsMDA-MB-231 and HepG2 cells were incubated in the presence of taxol or etoposide respectively under normoxia and hypoxia and apoptosis was analysed. A whole transcriptome analysis was performed in order to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 55 publications
8
69
0
1
Order By: Relevance
“…Our observations suggest that GPR87, GPR115 and/or TMEM45A may have similar functions in skin cancers. Interestingly, TMEM45A expression in primary human keratinocytes is induced upon differentiation [58]. These findings are in line with the results of our immunohistochemical analyses, showing increased TMEM45A staining from the basal layers of the epidermis to the stratum corneum (Figure 5c).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations suggest that GPR87, GPR115 and/or TMEM45A may have similar functions in skin cancers. Interestingly, TMEM45A expression in primary human keratinocytes is induced upon differentiation [58]. These findings are in line with the results of our immunohistochemical analyses, showing increased TMEM45A staining from the basal layers of the epidermis to the stratum corneum (Figure 5c).…”
Section: Resultssupporting
confidence: 90%
“…Thus, this gene and its protein product may play a role in immunity in the skin. A recent study reported that TMEM45A is overexpressed in breast cancer and is associated with poor prognosis in these patients [58]. Conversely, TMEM45A suppression promotes the progression of ductal carcinoma in situ to invasive breast cancer [59].…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms that TMEM45A expression in human keratinocytes, although present in subconfluent undifferentiated keratinocytes, is upregulated during epidermal differentiation, either induced by culture confluence or enhancement of Ca 2+ concentration in medium, as previously published . It also demonstrates strong connection between TMEM45A expression and keratinization, in both epidermis in vivo or during reconstruction in culture, but also in Hassal bodies inside the thymus.…”
Section: Discussionsupporting
confidence: 91%
“…Subcellular localization and functions remain unknown. Recently, we briefly reported selective induction of TMEM45A expression in differentiating keratinocytes, as well as increased expression in normal human epidermis , data later confirmed by others . Finally, in an approach using keratinocytes fractions purified from normal epidermis, TMEM45A was reported as a differentiation‐associated gene, because of its significantly higher mRNA level in granular and cornified keratinocytes‐enriched fraction compared with its level in basal keratinocytes‐enriched fraction .…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation